2020
DOI: 10.1007/s00296-020-04597-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost-effectiveness of physiotherapy interventions following total hip replacement: a systematic review and meta-analysis

Abstract: To examine the reported clinical and cost-effectiveness of physiotherapy interventions following total hip replacement (THR). A systematic review was completed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). MEDLINE, CINAHL, AMED, Scopus, DARE, HTA, and NHS EED databases were searched for studies on clinical and cost-effectiveness of physiotherapy in adults with THR published up to March 2020. Studies meeting the inclusion criteria were identified and key data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…While the benefits of physiotherapy after THA are generally acknowledged [ 1 ], and it frequently takes place in acute care clinics [ 17 , 18 ], there is a lack of consensus on the exact therapy program and only little evidence from controlled clinical trials, as a systematic review of the literature that appeared after 2008 [ 19 ] has shown. Other reviews and meta-analyses confirmed this view [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the benefits of physiotherapy after THA are generally acknowledged [ 1 ], and it frequently takes place in acute care clinics [ 17 , 18 ], there is a lack of consensus on the exact therapy program and only little evidence from controlled clinical trials, as a systematic review of the literature that appeared after 2008 [ 19 ] has shown. Other reviews and meta-analyses confirmed this view [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regaining a mobility level post-surgery that comes close to the patients’ previous mobility as a baseline is the goal. It is commonly accepted that physiotherapy after THA has a positive impact on muscle strength, range of motion, pain, or gait which all impact patient mobility [ 1 ]. Physiotherapy starts shortly after operation, primarily as inpatient therapy in the hospital where surgery took place [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, surgeons and physical therapists should consider assessing the risk of falls and fallinduced fractures after THA, especially in patients aged 65 years, as well as improving muscle strength and functional performance. Recently, Fatoye et al 17 ) have shown that 2-12 weeks of physiotherapy interventions might lead to improvements in hip muscle strength and functional performance in patients after THA. In addition, several studies reported that 4-10 weeks of home-based exercises showed similar functional improvements to outpatient physiotherapy interventions 18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that intense functional exercises require two weeks following hip and knee replacement, which results in skeletal muscle weakness. 34 Recent studies have shown that early postoperative hip and knee joint exercises should be carried out with proper intensity. The muscle training device used in this study forced the muscles to move around the ankle joint by means of equipment exercise and gradually restored the muscle strength through the ankle flexion and dorsiflexion exercises.…”
Section: Discussionmentioning
confidence: 99%